Science and art in the “Dutch period” in Northeast Brazil: the representation of cannibals and Africans as allies overseas - Phaf-Rheinberger, Ineke (Circumscribere International Journal for the History of Science, 2009)
Frans Post and Albert Eckhout painted landscapes and people in Brazil in the period of the optical technical revolution, which marked the “art of describing” in the Dutch Golden Age. Post’s and Eckhout’s pictures of cannibals have to be viewed within this tradition, in which a first modern and scientific model of caste society was represented. These images are not composed in order to shock the viewer but rather to let him repose and have time for studying them as epistemic objects. Although the social text of the body is addressed, this is not done with a critical tone. The cannibals fit perfectly well into the representation of Dutch urban society overseas in the seventeenth century